Developing an Assessment Model for Islamic Moderation Understanding of PTKI Students: Conceptual, Functional, and Procedural Dimensions - Susmiyati, Sri; Abdillah, Muhamad Hasan; Zurqoni, Zurqoni; Saugi, Wildan (el Buhuth: Borneo Journal of Islamic Studies, 2023)
This study aimed to develop and test an assessment model for Islamic moderation understanding of Islamic higher education (PTKI) students. The assessment model was developed based on the dimensions of Islamic moderation understanding which includes the dimensions of conceptual understanding, functional understanding, and procedural understanding. The subjects were students of Sultan Aji Muhammad Idris State Islamic University Samarinda, Tarbiyah College Balikpapan, and Islamic College Sangatta, with a total of 224 students. The data collection instrument used was a test instrument. The data obtained were then analyzed using the Confirmatory Factor Analysis technique with the LISREL 8.51 program. The results of the data analysis show that the assessment model developed for Islamic Moderation understanding of PTKI students has very good validity and reliability. All item items have a factor loading value of > 0.3 and the assessment model has a Goodness of Fit Index (GFI) > 0.90. Thus, the assessment model for Islamic moderation understanding is very appropriate to be used as a reference for further research because theoretically, it is in accordance with empirical data obtained from subjects in the field.